External quality assurance for HIV point-of-care testing in Africa: A collaborative country-partner approach to strengthen diagnostic services - Debrah I. Boeras (African Journal of Laboratory Medicine, 2016)
It is important to consider the role of diagnostics and the critical need for quality diagnostics services in resource-limited settings. Accurate diagnostic tests play a key role in patient management and the prevention and control of most infectious diseases. As countries plan for implementation of HIV early infant diagnosis and viral load point-of-care testing, the London School of Hygiene & Tropical Medicine has worked with countries and partners with an interest in external quality assurance to support quality point-of-care testing on the continent. Through a series of collaborative consultations and workshops, the London School of Hygiene & Tropical Medicine has gathered lessons learned, tools, and resources and developed quality assurance models that will support point-of-care testing. The London School of Hygiene & Tropical Medicine is committed to the continued advancement of laboratory diagnostics in Africa and quality laboratory services and point-of-care testing.